An automated sequential injection spectrophotometric method for evaluation of tyramine oxidase inhibitory activity of some flavonoids - Nuntaporn Moonrungsee (2018)
An automated sequential injection (SI) spectrophotometric system has been developed for evaluation of tyramine oxidase (TOD) inhibitory activity. The method is based on the inhibition of TOD that catalyzes the oxidation of tyramine substrate to produce aldehyde and hydrogen peroxide (H2O2). The produced H2O2reacts with vanillic acid and 4-aminoantipyrine (4-AA) in the presence of peroxidase (POD) to form a quinoneimine dye, the absorbance of which is measured of absorbance at wavelength of 490 nm. The decrease of the quinoneimine dye is related to an increase of TOD inhibitory activity. Under the optimum conditions: 1.0 mM tyramine, 8 U mL-1TOD, 1.0 mM vanillic acid, 1.0 mM 4-AA and delay time of 10 s, some flavonoid compounds were examined for the TOD inhibitory activity expressed as IC50value. It was found that flavonols (quercetin and myricetin) and flavans (epicatechin gallate (ECG) and epigallocatechin (EGC)) showed higher TOD inhibitory activity than flavones and flavanones. The results of IC50values obtained from the proposed method and a batch-wise method were not significantly different from each other. Moreover, the SI system enabled automation of the analysis, leading to more convenient, more sensitive and faster analysis than the batch-wise method. A precise timing of the system also improves precision and accuracy of the assay, especially when the measurement of absorbance at non-steady state condition is involved. © 2014 Published by Elsevier B.V.